Perlindungan Hukum Terhadap Konsumen Pengguna Kosmetik Yang Mengandung Bahan Berbahaya - Hendri Adi Suseno; Budi Handayani (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The purpose of this study is to discuss and analyze the impact caused by the circulation of cosmetic products that contain hazardous ingredients and discuss and analyze legal protection for consumers who use cosmetics that contain harmful ingredients. This research is included in normative juridical research. The results showed that the impact caused by the circulation of cosmetic products containing harmful ingredients is harmful to consumers as users. The impact includes: acne, allergies, skin irritation, burning, eye area infection and skin cancer if cosmetics are used for a long time. The results also show that legal protection for consumers who use cosmetics that contain harmful ingredients refers to Article 19 Paragraph 1 of Law Number 8 of 1999 concerning Consumer Protection which shows that business actors are responsible for providing compensation for damage, pollution, or loss suffered by consumers due to consuming goods / services produced or traded. This means that the compensation that must be borne by the manufacturer is in accordance with the damage, pollution or loss suffered by consumers after using these illegal cosmetic products. The compensation in question can be in the form of a refund or replacement of goods and/or services of similar or equivalent value, or health care and/or provision of compensation in accordance with the provisions of applicable laws and regulations. The compensation must be made within a grace period of 7 (seven) days after the transaction date.